Navigating the tech-savvy generation; key considerations in developing of an artificial intelligence curriculum - Ramli, Munasprianto; Fatra, Maifalinda; Murtadlo, Muhamad; Albana, Hasan; Hana Susanti, Baiq; Aldeia, Saifullah (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
The progress in artificial intelligence (AI) technology has greatly changed various facets of society. This study aimed to explore aspects that need to be considered in developing AI curriculum for senior high schools in Indonesia. The qualitative approach employed in this study. The researchers utilized focus group discussions with schools’ management and students at seven cities and group interviews with students at three cities. The results show that some schools want AI as an extracurricular activity, while others want it as a mandatory subject. School management and teachers aim for 2-3 competent AI instructors in each school. If no teachers are available, training will be provided to ICT, mathematics, or physics teachers for about a year to become AI educators. All participants agree on the importance of teaching students about AI applications and discussing ethical issues related to AI.